2022
DOI: 10.1007/s13555-022-00811-0
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Need in People with Psoriasis and Skin of Color in Canada and the United States

Abstract: The experience of dermatological conditions such as psoriasis is different for people with skin of color (SoC) than for white individuals. The objective of this literature review was to understand challenges and unmet needs associated with access to care, diagnosis, and treatment of psoriasis among people with SoC in Canada and the United States. The review focused on studies published in the last 5 years. After screening 919 unique records, 26 studies were included. Importantly, lack of culturally competent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…[1][2][3] Known differences exist regarding treatment outcomes for psoriasis patients with skin of color (SOC), with SOC patients reporting increased risk for hospitalization due to psoriasis and greater negative impact on quality of life. 4,5 Several possible explanations exist for this phenomenon. First, previous studies have suggested that dermatologists may underestimate the severity of psoriasis in patients with SOC due to differences in their cutaneous presentations compared to those in White patients.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3] Known differences exist regarding treatment outcomes for psoriasis patients with skin of color (SOC), with SOC patients reporting increased risk for hospitalization due to psoriasis and greater negative impact on quality of life. 4,5 Several possible explanations exist for this phenomenon. First, previous studies have suggested that dermatologists may underestimate the severity of psoriasis in patients with SOC due to differences in their cutaneous presentations compared to those in White patients.…”
Section: Introductionmentioning
confidence: 99%
“…6 For example, psoriasis plaques may be mistaken for post-inflammatory hyperpigmentation on black skin. [4][5][6] Patients with SOC may be underrepresented in clinical trials for psoriasis. 4,5,7 Furthermore, differences in socioeconomic status, access to health care, and lack of culturally competent care may contribute to worse treatment outcomes for patients of different races and ethnicities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations